372 The timing of pregnancy losses in beef cattle - Pohler, Ky G (J Anim Sci, 2020)
Pregnancy loss in beef cattle causes both management and economic challenges to a producer. Recent studies have been conducted to quantify reproductive failures that occur during fertilization, early embryonic development, and late embryonic/early fetal development periods of gestation in beef cattle. Minimizing reproductive inefficiency, specifically embryonic mortality (EM), is vital. Although fertilization rates are reportedly high in beef cattle, significant developmental failure occurs within the first 7 days of gestation. Approximately 28.4% of embryos will not develop past day 7 of gestation with most embryonic losses occurring before day 4. By the conclusion of the first month of gestation, 47.9% of cows submitted to a single insemination at day 0 will not be pregnant. Overall, late embryonic/fetal development between days 32 to 60 and 100 is 5.8% with a range of 3.2 to 42.7%. This talk will highlight some of the work our group is focusing on to determine timing and detection of pregnancy loss during these pivotal periods of pregnancy loss and potential management aspects to mitigate reproductive inefficiency. This was supported by Agriculture and Food Research Initiative Competitive Grant no. 2017-67015-26457 from the USDA National Institute of Food and Agriculture.